Investigation of manufacturing conditions of single roll rapidly solidified ribbon for anode materials of magnesium rechargeable batteries - Fuke, Kousuke; Suzuki, Mayumi; Tsukeda, Tadayoshi; Kurihara, Hideki; Kirimoto, Yuichi; Ikeda, Minoru; Nemoto, Yasunori; Tabata, Hironobu; Aida, Tetsuo (Journal of Japan Institute of Light Metals, 2023)
Magnesium rechargeable batteries are attracting attention as next-generation rechargeable batteries because of their resource abundance, cost, safety, and high electrical capacity per volume compared to conventional lithium-ion rechargeable batteries. Our joint research team focused not only on the electrochemically active magnesium composition of ribbon for the negative electrode materials of magnesium rechargeable batteries but also on the production process, focused on the single roll type liquid quenching and rapid solidification method, which can be produced at a lower cost. In this study, the optimal processing conditions were examined by comparing CAE analysis with ribbon actually manufactured, with the aim of further improving manufacturing conditions using the same method, such as length discontinuities, thickness, and surface properties of ribbon. We specifically various process parameters such as injection pressure and roll peripheral speed for evaluation. As a result, several linear cracks were observed on the surface of the ribbon as the peripheral speed increased and as the Gap became wider, and the surface properties tended to deteriorate. Also, It was found that the dominant factor in the length of the ribbon was the peripheral speed. As the peripheral speed increased, the length of the ribbon tended to increase.